2015
DOI: 10.1002/jbm.a.35601
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of self‐assembled IL‐1Ra‐presenting nanoparticles for the treatment of osteoarthritis

Abstract: Osteoarthritis is a progressive joint disease that results in degradation of cartilage in load-bearing joints. Pain and inflammation in the joint are the hallmarks of this condition, which further exacerbate the cartilage destruction and health of the patient. It is hence imperative to treat the joint inflammation at the earliest. Interleukin 1 (IL-1) blockade by IL-1 receptor antagonist (IL-1Ra) has shown promise in the clinic but this therapy suffers from rapid clearance, high doses, and frequent interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Although endogenously produced, exogenous administration IL-1Ra proteins into the joint space have shown to effectively inhibit inflammation. Rather than direct injection, studies have employed microspheres [61] or self-assembling nanoparticles that encapsulate [62] or have the protein tethered on the surface [63,64]. Whitmire et al, and Wang et al, confirmed vehicle-mediated IL-1R retention in normal rat knee joints, while Elsaid et al, observed the disease-modifying effect of PLGA microsphere-encapsulated IL-1R in the rat anterior cruciate ligament transection (ACLT) OA model.…”
Section: Disease-modifying Treatmentsmentioning
confidence: 99%
“…Although endogenously produced, exogenous administration IL-1Ra proteins into the joint space have shown to effectively inhibit inflammation. Rather than direct injection, studies have employed microspheres [61] or self-assembling nanoparticles that encapsulate [62] or have the protein tethered on the surface [63,64]. Whitmire et al, and Wang et al, confirmed vehicle-mediated IL-1R retention in normal rat knee joints, while Elsaid et al, observed the disease-modifying effect of PLGA microsphere-encapsulated IL-1R in the rat anterior cruciate ligament transection (ACLT) OA model.…”
Section: Disease-modifying Treatmentsmentioning
confidence: 99%
“…To counteract IL‐1 signalling, IL‐1 receptor antagonist‐poly(2‐hydroxyethyl methacrylate)‐pyridine nanoparticles were constructed and shown to be stable for several days and to efficiently block IL‐1β signalling (Agarwal et al . ). Similarly, a block copolymer efficiently bound IL‐1receptor antagonist and had the same effect in a rat stifle joint maintaining a higher half‐life than its soluble counterpart (~3 times more) (Whitmire et al .…”
Section: Nanotechnological Approachesmentioning
confidence: 97%
“…The strong pro-inflammatory effect of IL-1β can also be blocked by the IL-1 receptor antagonist (IL-1ra), which is a receptor naturally secreted by polymorphonuclear cells after their stimulation that has been effectively used in the clinic as a recombinant protein (Anakinra ® ) [111,112]. In the context of OA, IL-1Ra-poly(2-hydroxyethyl methacrylate)-pyridine NPs have been developed and tested in vitro on RAW 264.7 macrophage-like cells and a B-cell precursor acute lymphoblastic leukemia cell line (EU1), showing no toxicity on the former and a significant reduction of NF-κβ activation upon IL-1β stimulation [113]. Another approach consisted of the development of polymeric NPs to target the A2A adenosine receptor, as it has been demonstrated that mice with impaired adenosine signaling within macrophages of the joints develop OA spontaneously [114].…”
Section: Polymeric Nanoparticles Loaded With Other Anti-inflammatory mentioning
confidence: 99%